2002
DOI: 10.1172/jci0216001
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ABCG5 and ABCG8 promotes biliary cholesterol secretion and reduces fractional absorption of dietary cholesterol

Abstract: IntroductionMultiple physiological mechanisms limit the entry of dietary sterols into the bloodstream. Excess cholesterol is removed from the body either by direct secretion into the bile or after conversion to bile acids. Although the mechanisms by which dietary sterols are absorbed by the intestine and secreted into the bile have been well characterized physiologically, the machinery responsible for these two processes has not been molecularly defined. The most abundant sterols in the human diet are choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
268
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(288 citation statements)
references
References 36 publications
17
268
0
3
Order By: Relevance
“…Nevertheless, unesterified cholesterol can also be transported back into the intestinal tract through ATP-binding cassette (ABC) transporters, such as ABCG5 and ABCG8 (10,76). Furthermore, growing evidence supports the role of other transporters, such as ATP-binding cassette transporter A1 (ABCA1), the scavenger receptors CD36 and class B type I (SR-BI), the membrane-bound ectoenzyme aminopeptidase N (APN), the human P-glycoprotein (Pgp) or ABCB1 and the microsomal triacylglycerol transfer protein (MTP) (34), but their significance is not clearly defined yet (6).…”
Section: Intestinal Cholesterol Absorptionmentioning
confidence: 99%
“…Nevertheless, unesterified cholesterol can also be transported back into the intestinal tract through ATP-binding cassette (ABC) transporters, such as ABCG5 and ABCG8 (10,76). Furthermore, growing evidence supports the role of other transporters, such as ATP-binding cassette transporter A1 (ABCA1), the scavenger receptors CD36 and class B type I (SR-BI), the membrane-bound ectoenzyme aminopeptidase N (APN), the human P-glycoprotein (Pgp) or ABCB1 and the microsomal triacylglycerol transfer protein (MTP) (34), but their significance is not clearly defined yet (6).…”
Section: Intestinal Cholesterol Absorptionmentioning
confidence: 99%
“…This effect appears to depend on the ability of LXRs to induce transcription of the ABCG5 and ABCG8 transporter in the liver and intestines, resulting in increased cholesterol excretion into the bile and decreased cholesterol absorption, respectively [15,32]. Consistent with these studies, deficiency of ABCG5 and ABCG8 in a rare genetic disorder known as sitosterolemia results in increased absorption of cholesterol from the intestine, diminished secretion of sterols into bile, hypercholesterolemia, and subsequent premature cardiovascular disease [33].…”
Section: Bile Acid Synthesis and Secretionmentioning
confidence: 75%
“…GBEC probably contribute to cholesterol efflux into bile via ABCG5 and ABCG8, in a manner analogous to the function of this twinned sterol transporter at the canalicular pole of hepatocytes. In previous studies, ABCG5 and ABCG8 were found to move from the cytoplasm to the apical membrane upon LXRa/RXR ligand treatment [1,12]. The mixed bile salt micelles found in the gallbladder lumen are likely to result from ABCG5/ABCG8-mediated cholesterol efflux [19].…”
Section: Discussionmentioning
confidence: 88%
“…These cholesterol efflux pathways include unmediated diffusion [8] and proteinmediated transport by scavenger receptor BI (SR-BI) or ATP-binding cassette transporter A1 (ABCA1) [9,10]. ABCG5 and ABCG8 form heterodimers that are expressed on the canalicular membranes of hepatocytes, where they excrete cholesterol into bile [11,12]. It has been suggested that ABCG5/ABCG8 play a role in sterol flux at the apical pole of polarized epithelial cells in the liver.…”
Section: Introductionmentioning
confidence: 99%